THE IMPORTANCE OF WORKING MEMORY IN ACQUIRING SECOND LANGUAGE (L2) - Hermagustiana, Istanti (Fakultas Ilmu Budaya, Universitas Mulawarman, 2018)
This paper highlights the importance of short term memory and its roles in linking the information acquired from sensory memory into long term memory. Short term-memory, also known as working memory, has significant contribution to transfer information as it is the location where many forms of complex thinking such as problem solving, contemplation, and language comprehension occur. In addition, the instrumental role of working memory in the acquisition of second language will be discussed.